2017
DOI: 10.1016/j.cgh.2016.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab-Induced Colitis Treated by Infliximab

Abstract: A 51-year-old man was admitted to our institution for abdominal pain and bloody diarrhea. The patient had been diagnosed as having uveal melanoma of the right eye 17 years previously, which had been treated by enucleation and radiotherapy. Because of the recurrent melanoma in the right orbit with multiple metastases in the liver and stomach, immunotherapy with triweekly infusion of nivolumab (200 mg, 2 mg/kg) was started. After the fourth infusion of nivolumab, he manifested abdominal pain and bloody diarrhea.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 5 publications
(5 reference statements)
1
44
0
Order By: Relevance
“…1d). According to recent reports [710], similar findings were observed following treatment with nivolumab. We observed the same clinical findings, which included continuous mucosal inflammation, in the patients described in this study (Table 1).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…1d). According to recent reports [710], similar findings were observed following treatment with nivolumab. We observed the same clinical findings, which included continuous mucosal inflammation, in the patients described in this study (Table 1).…”
Section: Discussionsupporting
confidence: 78%
“…As neither is a characteristic finding, it is difficult to differentiate based on pathological findings. However, Yanai et al reported that prominent apoptosis in the colorectal epithelium appears to be a characteristic histological finding of nivolumab-induced colitis [10]. To clarify the differences between UC and nivolumab-induced colitis, further evidence derived from reported cases is needed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, enterocolitis has been reported in up to approximately 8$ of patients who have received ipilimumab [5]. In contrast, nivolumab-induced colitis is rare, and only 2 cases have been reported to date [6, 7]. As ipilimumab is a monoclonal antibody against CTLA-4, which negatively regulates T-cell activation, ipilimumab-induced colitis might result from an increase in cytotoxic CD8+ T cells relative to regulatory FoxP3+ T cells in the colon [8].…”
Section: Discussionmentioning
confidence: 99%